2021
DOI: 10.1002/adpr.202000178
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide for Perovskite Photovoltaic Cells

Abstract: Organic–inorganic perovskite solar cells (PSCs) have shown tremendous progress from 3.8% power conversion efficiency (PCE) in 2003 to 25.2% in 2020 because of their wide range of light absorption, fast charge separation, long carrier diffusion length, and long carrier lifetime. The optoelectronic characteristics of hole transport material (HTM) and electron transport material (ETM) strongly affect photovoltaic (PV) performance and stability of PSCs. Recently, various inorganic HTMs with high efficiency, stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 190 publications
1
20
0
Order By: Relevance
“…Importantly, the time-resolved analysis also proves that high non-radiative recombination is responsible for the fast decay of the reference cell of Fig. 2d , that therefore cannot be attributed to carrier extraction as sometimes reported in the literature 31 , 32 .…”
Section: Resultssupporting
confidence: 78%
“…Importantly, the time-resolved analysis also proves that high non-radiative recombination is responsible for the fast decay of the reference cell of Fig. 2d , that therefore cannot be attributed to carrier extraction as sometimes reported in the literature 31 , 32 .…”
Section: Resultssupporting
confidence: 78%
“…Another factor limiting V oc is the band offset of the valence band maximum between perovskites and NiO x , which shrinks the quasi-Fermi-level splitting. 67,68 Thus, this energy level misalignment limits the further increase in V oc despite the low defect density in the MWA-TOPO film.…”
Section: Resultsmentioning
confidence: 99%
“…Although inorganic HTLs (such as NiO x ) possess a high thermal stability and transparency, [ 68–70 ] their PV performance is usually inferior to their organic counterparts due to relatively a low intrinsic conductivity and surface defects. [ 71,72 ] For instance, it was reported that NiO x Ni ≥3+ surface species can react with perovskite organoiodide precursors, resulting in a defective NiO x /perovskite interface. [ 73 ] Besides, most of the inorganic HTLs require either a high‐temperature or high‐vacuum processing step and may feature a poor wettability with respect to the perovskite precursor ink, in case of solution processing.…”
Section: Introductionmentioning
confidence: 99%